PENGARUH TOTAL ASSET TURN OVER DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA PT INDOFOOD SUKSES MAKMUR TBK, PT MAYORA INDAH TBK, PT NIPPON INDOSARI CORPINDO TBK PERIODE 2013-2022 - Fauziah, Sifa; Mutawali (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Total Asset Turnover and Debt to Assets Ratio on Return on Assets at PT Indofood Sukses Makmur Tbk, PT Mayora Indah Tbk, and PT Nippon Indosari Corpindo Tbk for the 2013-2022 period. The research method used is a descriptive method with a quantitative approach. The population in this research is the financial reports of PT Indofood Sukses Makmur Tbk, PT Mayora Indah Tbk, and PT Nippon Indosari Corpindo Tbk. The method used in this research is multiple regression analysis, classical assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. Significant tests include the t statistical test and the f statistical test, as well as coefficient of determination. The data was processed and analyzed using the Eviews 12 program. The results of this research show that partially Total Asset Turnover has a significant effect on Return on Assets, with a significant value of 0.0003. Partially the Debt to Asset Ratio has no effect on Return on Assets, with a significant value of 0.5928. Simultaneously Total Asset Turnover and Debt to Asset Ratio have a significant effect on Return on Assets.